2002
DOI: 10.1037/1524-9220.3.1.51
|View full text |Cite
|
Sign up to set email alerts
|

Masculine gender role conflict and stress in relation to parental attachment and separation.

Abstract: In this study, the authors hypothesized that men's own gender role strain and estimates of their fathers' gender role strain, would be associated with less attachment to, and more psychological separation from, their parents. Two hundred four college students completed the Gender-Role Conflict Scale, the Masculine Gender Role Stress Scale, the Parental Attachment Questionnaire, and the Psychological Separation Inventory. Results indicate that (a) men who perceived their fathers as having less gender role confl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
41
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 46 publications
2
41
0
Order By: Relevance
“…Finally, in this study majority of respondents were female. Previous studies (DeFranc & Mahalik, 2002;Ross & Fuertes, 2010;Sprecher & Sedikides, 1993) indicated that female express themselves more than men and reported more attachment to their families which may have an effect on the result of the study.…”
Section: Discussionmentioning
confidence: 79%
“…Finally, in this study majority of respondents were female. Previous studies (DeFranc & Mahalik, 2002;Ross & Fuertes, 2010;Sprecher & Sedikides, 1993) indicated that female express themselves more than men and reported more attachment to their families which may have an effect on the result of the study.…”
Section: Discussionmentioning
confidence: 79%
“…A large body of literature has documented the negative consequences of adhering to masculine gender roles on men's mental health (see Pleck 1981 for a review). These consequences include alcoholism (Lemle and Mishkind 1989), depression (Good and Wood 1995;Good et al 2004;Mahalik and Rochlen 2006), restriction on expressions of emotion generally (O'Neil 1981(O'Neil , 1998, and within familial relationships specifically (DeFranc and Mahalik, 2002;Mahalik and Morrison 2006). Given the negative consequences associated with adherence to hegemonic masculinity, feminist engagement on the part of men can be a more constructive (and social justice oriented) response to the oppressive restrictiveness of masculinity as a social construct.…”
Section: Introductionmentioning
confidence: 99%
“…The impact of this separation may be comparatively less intense for boys who are socialised to tolerate separation from and to be less emotionally connected to their parents (e.g. DeFranc & Mahalik, 2002). Research on differences in autonomy granting has demonstrated that girls tend to be socialised towards compliance and intimacy while boys are socialised to be independent (e.g.…”
mentioning
confidence: 99%